Stability and Controllability of Various Spatial Solitons in Exciton–Polariton Condensates by a Composite Pumping - Zhang, Kun; Wen, Wen; Lin, Ji; Li, Hui-jun (Frontiers in Physics, 2022)
We investigate the stability and controllability of one-dimensional bright and dark solitons, and two-dimensional bright solitons and vortices with the charges m = 1 and 2, respectively, in a nonresonantly incoherent pumped exciton–polariton condensates. A composite pumping, consisting of the constant part and the Bessel-type spatially modulating part, is introduced to balance the gain and loss. We demonstrate that the pumping can not only stabilize all these solitons but also modulate the profiles of these solitons. We also find that all these solitons obtained in this study are different from the ones in the previous studies. Our work may pave a way to modulate these solitons in the nonresonantly pumped exciton–polariton system.